Formation and promotion of the employer brand - Zhong Leyu (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the research is a system of employer brand building and fostering within modern enterprises. The subject of the research peculiarities of employer brand formation mechanism within HeyTea company. The purpose of the master's thesis is to explore HeyTea’s practices and strategies in reinforcing employer brand image, analyze the effectiveness of its marketing mechanisms, and propose suggestions for further development. Based on the results of the study theoretical and practical provisions regarding the optimization of employer brand formation at enterprise were put forward. The practical significance of the research results consists in that they will contribute to the improvement of the enterprise brand image formation expertise and in thereby boost its competitive edge on the Chinese market. The obtained results hold practical significance as the key provisions and conclusions of the research are translated into recommendations for business brand image reinforcement within HeyTea enterprise.
Scientific advisor: Semenchenko T., PhD in education, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; employer brand; HR brand; company; target audience; employee; branding